STRATEGI USAHA PEDAGANG KAKI LIMA (PKL) DI KOTA METRO: PASCA PANDEMI COVID-19: (Studi Kasus pada PKL di Jl. Kihajar Dewantara Metro Timur) - Ditta Nurhidayanti; Estelee Elora Akbar (Politeknik Negeri Ambon, 2023)
The purpose of this study is to identify and analyze the sales strategies of street vendors (PKL) in Metro City: Post-covid-19 pandemic. This research was conducted on Jl. Ki Hajar Dewantara, East Metro sub-district, Metro City, Lampung Province. This type of research is descriptive qualitative research. The data source used is the primary data source. Collecting data in this study using observation, interviews and documentation. The results that can be concluded in this study are identifying trading strategies that must be implemented by street vendors who are affected by Covid 19. At the beginning of the pandemic, their income had decreased but over time they were able to get up and maintain their business. The strategy for street vendors on Jl. Ki Hajar Dewantara in maintaining his business in the midst of the Covid 19 pandemic, including by expanding market share by going online, creating new products and cooperating with other business actors.